2020
DOI: 10.1111/jog.14569
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormality: Prevalence, prenatal diagnosis and associated anomalies based on a provincial‐wide birth defects monitoring system

Abstract: Aim To investigate the epidemiology of chromosomal abnormalities (CA) in fetuses of all pregnancies based on a provincial‐wide birth defects‐monitoring system, which could provide scientific basis for making relatively policy and research. Methods Chromosomal abnormalities cases were collected from all hospitals in Hunan Province, China, between 2016 and 2019. The prevalence of CAs was calculated to examine associations among infant sex, maternal age and region. The rates of prenatal diagnosis and termination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…[11][12][13] Many studies in the literature have revealed the incidence of prenatal chromosomal anomalies. [14][15][16][17][18][19] However, few studies have focused on postnatal chromosomal abnormalities. 20,21 In this study to fill this gap in the literature, we aimed to reveal the postnatal chromosomal anomaly rate in our cohort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Many studies in the literature have revealed the incidence of prenatal chromosomal anomalies. [14][15][16][17][18][19] However, few studies have focused on postnatal chromosomal abnormalities. 20,21 In this study to fill this gap in the literature, we aimed to reveal the postnatal chromosomal anomaly rate in our cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chromosomal abnormalities that cause symptoms such as amenorrhea, recurrent pregnancy loss, and infertility can be diagnosed in the pubertal and post‐pubertal period, which is usually the period when their complaints occur 11–13 . Many studies in the literature have revealed the incidence of prenatal chromosomal anomalies 14–19 …”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of congenital disability cases have unknown causes; however, strong evidence suggests that genetic conditions contribute to their etiologies ( Feldkamp et al, 2017 ; Sun et al, 2018 ). Chromosomal abnormalities such as trisomies 21 (T21), 18 (T18), and 13 (T13) and sex chromosome aneuploidies (SCAs) are the main causes of congenital disabilities ( Xie et al, 2021 ). In addition, multiple lines of evidence indicate that copy number variants (CNVs) in submicroscopic chromosomal structures can also play an important role in the etiology of some congenital disability cases ( Lupo et al, 2019 ) ( Hobbs et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal abnormalities are seen in 11-55 of 10 000 births and adversely affect fetal and postnatal life, causing mortality or severe morbidities. 1,2 The most common chromosomal abnormalities are Trisomy 21, Trisomy 18, and Trisomy 13, seen in 1/700, 1/2500, and 1/5000 births, respectively. [3][4][5] Prenatal screening is established for these major abnormalities using serum markers, fetal DNA in maternal blood, and ultrasound findings.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal abnormalities are seen in 11–55 of 10 000 births and adversely affect fetal and postnatal life, causing mortality or severe morbidities 1,2 . The most common chromosomal abnormalities are Trisomy 21, Trisomy 18, and Trisomy 13, seen in 1/700, 1/2500, and 1/5000 births, respectively 3–5 .…”
Section: Introductionmentioning
confidence: 99%